KLASIFIKASI SEKTOR INDUSTRI KOTA BANDUNG BERDASARKAN METODE KESEBANDINGAN MODEL INPUT OUTPUT - Teti Sofia Yanti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: The preparation of input output tables aims to present a picture of the interrelationships and interconnections among sector units in the economy as a whole, so that the input output model is a complete and comprehensive analysis tool. For the purposes of planning and evaluating the overall development outcomes of both national and smaller scale (district / city level), the regional development planning approach model can use an input-output analysis model. Through the analysis of the location quention can be seen the diversity of the economic base of a region's society. Against the areas analyzed can be classified sectors that are able to compete in their own territory or that can compete with other regions. Based on the analysis of 40 economic sectors in Bandung, as many as 16 sectors able to compete with other regions, and the rest can only compete in the area of Bandung.Keywords: Output Input Model, Location Quotient, Industry Classification, Output, Labor